Isolation of gene encoding cis-prenyltransferase 4 (CPT4) from rubber tree (Hevea brasiliensis) - Huynh Cam Tu, Nguyen; Thi My Binh, Pham; Thanh Luong, Tran; Thanh, Tran; Thi Hong Thuong, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2017)
Cis -prenyltransferase (CPT) catalyzes consecutive cis -consendation reactions of isopentenyl diphosphate (IPP) with allylic diphosphate acceptors to synthesize cis -prenyldiphosphates with a certain chain length. With the exception of HRT1 and HRT2 which shown to be a part of rubber biosynthetic machinery, the biochemical functions of other CPTs remain unknown. By using HRT2 as a query sequence for TBLASTX searches against the recently released transcriptome database of Hevea brasiliensis , we identified six contigs, one of which contains a sequence encoding for a protein that shares 75% identity to a previously reported cis -prenyltransferase, HRT2. This coding sequence, designated as HbCPT4, was successfully isolated from the latex of Hevea brasiliensis RRIV 209 plants and sequenced. A comparison of the full-length sequences of the HbCPT4 CDS obtained by PCR and the HbCPT4 CDS predicted by bioinformatics analysis revealed seven nucleotides that were different, but none of them leading to the changes in the amino acid sequence. The deduced protein sequence has 296 amino acid residues, a predicted mass of 34 kDa, and a pI of 8.19. It also contains five conserved regions (I–V regions) related to catalytic activity and substrate binding of cis- prenyltransferases.